logo for solving-math-problems.com
leftimage for solving-math-problems.com

Making a letter the subject

how do i do it?

how do i do it?











































How do i do the equation in the picture>?

a = (6a - n)/(3 + n)

Solve for "a", and then solve for "n",

Begin by multiplying each side of the equation by (3 + n).

Comments for Making a letter the subject

Click here to add your own comments

Apr 06, 2011
Making a letter the subject
by: Staff


The question:

a = (6a – n) ÷ (3 + n)

how do I do it?



The answer:


a = (6a – n) ÷ (3 + n)

a = (6a – n)/(3 + n)

Part I: solve for “a”
Part II: solve for “n”


Part I: solve for “a”

a = (6a – n)/(3 + n)

Multiply each side of the equation by (3 + n)

a * (3 + n) = [(6a – n)/(3 + n)]* (3 + n)

a * (3 + n) = (6a – n)* [(3 + n)/(3 + n)]

a * (3 + n) = (6a – n)* 1

a * (3 + n) = 6a – n

3a + an = 6a – n

Add -6a to each side of the equation

3a - 6a + an = 6a - 6a – n

3a - 6a + an = 0 – n

3a - 6a + an = – n

-3a + an = – n

Factor “a” from the expression (-3a + an) on the left hand side of the equation using the distributive law

a * (-3 + n) = – n

a * (n - 3) = – n

Divide each side of the equation by (n – 3)

a * (n - 3)/(n – 3) = – n/(n – 3)

a * 1 = – n/(n – 3)

a = – n/(n – 3)



Part II: solve for “n”

a = (6a – n)/(3 + n)

Multiply each side of the equation by (3 + n)

a * (3 + n) = [(6a – n)/(3 + n)]* (3 + n)

a * (3 + n) = (6a – n)* [(3 + n)/(3 + n)]

a * (3 + n) = (6a – n)* 1

a * (3 + n) = 6a – n

Use the distributive law to eliminate the parentheses on the left side of the equation

3a + an = 6a – n

Add -3a to each side of the equation

3a – 3a + an = 6a – 3a – n

0 + an = 6a – 3a – n

an = 6a – 3a – n

an = 3a – n

Add +n to each side of the equation

an + n = 3a – n + n

an + n = 3a + 0

an + n = 3a

Factor “n” from the expression (an + n) on the left hand side of the equation using the distributive law

n * (a + 1) = 3a

Divide each side of the equation by (a + 1)

n * (a + 1)/(a + 1) = 3a/(a + 1)

n * 1 = 3a/(a + 1)

n = 3a/(a + 1)


the final answer is:

a = – n/(n – 3)

n = 3a/(a + 1)



Thanks for writing.


Staff
www.solving-math-problems.com


Click here to add your own comments

Join in and write your own page! It's easy to do. How? Simply click here to return to Math Questions & Comments - 01.



Copyright © 2008-2015. All rights reserved. Solving-Math-Problems.com